Local spin: A treatment beyond single determinant wave functions - Alcoba, Diego Ricardo (2009)
This Letter describes a partitioning of the expectation value 〈 over(S, ^) 2 〉 of an N-electron system (molecule, ion, radical, etc.) into one- and two-center contributions. The proposal is valid for both independent and correlated particle models of the wave function. Our procedure provides local spin results which are physically reasonable for closed and open shell systems. Numerical results of the electronic spin population analyses of selected systems in the Hilbert space of atomic orbitals, arising from both single determinant wave functions and multideterminantal ones are analyzed and compared. © 2009 Elsevier B.V. All rights reserved.